Epigenetic methylation in Eosinophilic Esophagitis: Molecular ageing and novel biomarkers for treatment response. Issue 12 (6th November 2020) - Jensen, Elizabeth T.; Langefeld, Carl D.; Zimmerman, Kip D.; Howard, Timothy D.; Dellon, Evan S.
Abstract: Background: Treatment failure in eosinophilic esophagitis (EoE) is common. We hypothesize that DNA methylation differs between patients by treatment response to topical steroids (oral viscous budesonide), thus offering the potential to inform targeting therapies. Objective: We sought to identify differentially methylated sites and affiliated genes in pre‐treatment oesophageal cells between responders and non‐responders and test for accelerated epigenetic ageing in oesophageal cells of EoE patients. Methods: DNA was extracted from prospectively collected and biobanked oesophageal biopsies from 36 Caucasian treatment naïve EoE patients at diagnosis. Methylation assays were completed using the Infinium HumanMethylation450 BeadChip. Normalized β values for each CpG site were tested (t test) for differential methylation. Further, 353 CpG probes were used to estimate epigenetic age for each patient and a linear regression model tested whether chronologic age and epigenetic age differed. Epigenetic age results were confirmed in an independent cohort of healthy controls. Results: Eighteen CpG sites were differentially methylated by treatment response ( P  < .00001). The mean epigenetic age and chronological age were 56.1 ± 11.1 and 36.7 ± 12.3 years, a mean age difference of 19.3 ± 5.2 years ( P  < .0001); accelerated ageing was not observed in the oesophageal cells of healthy controls. Conclusions and clinical relevance: EoE patients that respond versus do not respond to treatment have differences in their methylation profile, including enrichment of genes in pathways consistent with cellular injury and repair due to environmental stress and cell adhesion and barrier integrity. EoE also appears to accelerate cellular ageing. Whether treatment can arrest or reverse accelerated epigenetic ageing and the implications for long‐term disease progression is important areas for future research.